ANALISIS STRATEGI PENGEMBANGAN USAHA BUDIDAYA JAMUR MERANG (Volvariella volvacea) STUDI KASUS DI PONDOK PESANTREN ANWAR FUTUHIYAH SLEMAN YOGYAKARTA - Sigit Nugroho; Marosimy Millaty (Agros Journal of Agriculture Science, 2023)
The Anwar Futuhiyyah Islamic boarding school is one of the Islamic boarding schools that has a business entity engaged in agriculture that cultivates straw mushrooms. This research aims to identify internal and external factors and determine alternative strategies for developing straw mushroom cultivation in the Islamic boarding school environment. Primary and secondary data were used through direct interviews and distributing questionnaires to mushroom managers at the Anwar Futuhiyyah Islamic Boarding School. The data analysis method used is SWOT analysis. The results of the EFAS and IFAS matrix analysis place the mushroom business in quadrant I, which shows significant potential and opportunities. These opportunities can be optimized by implementing aggressive strategies that will enable full utilization of the strengths possessed by the mushroom cultivation business. Analysis of the development strategy carried out in the straw mushroom business in Pondok Anwar Futuhiyyah using the SWOT matrix formulation, namely the SO strategy which consists of increasing the quality and quantity of production and harvest of straw mushrooms, involving competent boarding school students to obtain quality mushroom production results, making various kinds innovation in processed products made from straw mushrooms, developing access to information and marketing areas for straw mushrooms, developing straw mushroom center areas into mushroom agrotourism. Key-words: Development strategy, Straw mushroom, SWOT AnalysisINTISARI Pondok pesantren Anwar Futuhiyyah merupakan salah satu pondok pesantren yang memiliki badan usaha yang bergerak dibidang pertanian yang membudidayakan jamur merang. Penelitian ini bertujuan untuk identifikasi faktor internal dan eksternal serta mengetahui alternatif strategi pengembangan budidaya jamur merang di lingkungan pesantren. Data primer dan sekunder digunakan melalui wawancara secara langsung dan penyebaran kuisioner kepada pengelola jamur merang di Pondok Pesantren Anwar Futuhiyyah. Metode analisis data yang digunakan adalah analisis SWOT. Hasil analisis matriks EFAS dan IFAS menempatkan usaha jamur merang pada kuadran I, yang menunjukkan adanya potensi dan peluang yang signifikan. Peluang tersebut dapat dioptimalkan dengan penerapan strategi agresif yang akan memungkinkan pemanfaatan sepenuhnya dari kekuatan yang dimiliki oleh usaha budidaya jamur merang. Analisis strategi pengembangan yang dilakukan pada usaha jamur merang di Pondok Anwar Futuhiyyah menggunakan rumusan matriks SWOT yaitu strategi SO yang terdiri dari peningkatan kualitas dan kuantitas produksi dan hasil panen jamur merang, melibatkan santri pondok yang berkompeten untuk mendapatkan hasil produksi jamur yang berkualitas, membuat berbagai macam inovasi produk olahan berbahan baku jamur merang, pengembangan akses informasi dan wilayah pemasaran jamur merang, pengembangan kawasan sentra jamur merang menjadi agrowisata jamur.  Kata kunci: Analisis SWOT, Jamur merang,  Strategi pengembangan